Toxicity of nitrite and its histopathological effects on the gills of mud crab Scylla serrata (forskal) larvae and juveniles. - Abiera, Mary Lynn S. (Miagao, Iloilo University of the Philippines, 2008)
Studies on the acute toxicity of nitrite at different salinity levels and its histopathological effects on the gills were conducted on mud crab Scylla serrate larvae and juveniles. Early larval stages of mud crab S. serrata were exposed to different concentrations of nitrite (40, 80, and 160 mgL-1 and a control, without added nitrite) and three salinity levels (25, 30 and 35 gL-1 ) using a static renewal method. Estimated LT50 in toxicity test decreased in all stages with increasing nitrite concentration in all salinity levels. Percentage survivalin all stages decreased in all treatments with exposure time. There was no significant interaction between salinity and nitrite on survival, LT50 and LC50 values of NO2-N in S. serrate larvae (P>0.05). The chloridecomponent of salinity within 25 to 35 gL-1 did not seem as effective in alleviating nitrite toxicity. Based on 96 h LC50 of zoea 3, the stage of larvae which appeared to be most sensitive, and an application factor of 0.1, the 'safe' level of rearing mud crab larvae was calculated to be 2.55mgL-1 NO2-N. To observe histopathological conditions of mud crab, s. serrate juveniles were exposed to the same concentrations of nitrite and salinity levels used in the toxicity testin larvae.. There was no significant interaction between salinity and nitrite on the prevalence and severity of histopathological lesions in the gills of mud crab juveniles (P>0.05), but a highlysignificant (P<0.01) interaction between exposure time and nitrite concentration was shown. Histopathological and proliferation, epithelial lifting, epithelial disruption, lamellar telangiectasisandvacuolation. Observed histopathological changes are discussed in terms of its effect on the functions of the gills in respiration, osmoregulation and excretion.
Dissertation (Doctor of Philosophy in Fisheries Aquaculture -- U.P. in the Visayas, April 2008.
Keywords: Toxicity; histopathological; Mud crab